2020
DOI: 10.14569/ijacsa.2020.0111269
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Smart Weighted and Neighborhood-enabled Load Balancing Scheme for Constraint Oriented Networks

Abstract: In Wireless Sensor Networks (WSNs), uniform load or traffic distribution strategy is one of the main challenging issues, which is tightly coupled with the resource-limited networks. To address this problem, various mechanisms have been developed and presented in the literature. However, these approaches were either application specific that is designed for a specific application area such as smart building or overlay complex. Therefore, a simplified and energy efficient loadbalancing scheme is always needed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Authors have suggested a disease-diagnostic paradigm for intelligent healthcare systems that is supported by artificial intelligence and the Internet of Things (IoT) and integrates data from multiple sources, including wearable devices, smartphones, and environmental sensors [24][25][26][27][28][29][30][31][32]. Researchers have provided an overview of the key concepts and technologies involved in AIoT healthcare architectures and highlighted the potential benefits of AIoT healthcare architectures, including improved patient care, reduced costs, and increased efficiency [33][34][35][36][37][38][39][40][41][42].…”
Section: Healthcare With Emotional Intelligence In Iotmentioning
confidence: 99%
“…Authors have suggested a disease-diagnostic paradigm for intelligent healthcare systems that is supported by artificial intelligence and the Internet of Things (IoT) and integrates data from multiple sources, including wearable devices, smartphones, and environmental sensors [24][25][26][27][28][29][30][31][32]. Researchers have provided an overview of the key concepts and technologies involved in AIoT healthcare architectures and highlighted the potential benefits of AIoT healthcare architectures, including improved patient care, reduced costs, and increased efficiency [33][34][35][36][37][38][39][40][41][42].…”
Section: Healthcare With Emotional Intelligence In Iotmentioning
confidence: 99%
“…HYPOTHESES AND EVIDENCE SUMMARY [12] Hypotheses Findings Evidence H1. The greater the integration of IS, the greater the investment in countermeasures.…”
Section: Table Imentioning
confidence: 99%
“…Recently, cyberattacks have increased due to advances in the technologies used in most information systems. Consequently, most organizations need to invest in cybersecurity and employee training to raise awareness of the importance of securing systems and their sensitive information [12]. One approach to protecting information systems was suggested by [13], which suggested that integrating information systems across organizational environments can improve cybersecurity.…”
Section: Cybersecuritymentioning
confidence: 99%